Shaping Our Australian Scenographic Identities: A visual essay. Issue 1 (1st December 2021) - Rixon, Tessa; Irwin, Jennifer; Walters, David; Neideck, Jeremy; McKeague, M'ck; Roberts, Richard; Brumpton, Anthony; Taumoepeau, Latai
In the form of a visual essay, this reflection charts a course through eight specific moments in Australian performance design history. Selected by guest editor Tessa Rixon, this essay features contributions from Australia's most established designers from sound, lighting and costume through to the latest in performance design practice and research. Specially curated for this special edition on Australian scenography, each contributor reflects on a personal experience of a pivotal performance design from their own practice or their experience as an audience member. The resulting contributions present a mix of design forms and focuses, across all forms of live performance ‐ mainstage theatre, independent site-specific performance, queer theatre, Indigenous theatre, Indigenous dance, scenography for performance beyond the stage frame, performance in response to the climate crisis and finally, a few pivotal stepping stones in our national scenographic identity ‐ from the very personal, to the very global. These exemplars of design practice shape what we now could call Australian scenography.